Grandma Elephant's in Charge - Jenkins, Martin (Cambridge, MA Candlewick Press, 2003)
Describes the behavior of elephants in a family group, particularly the role of the older female elephants.
Fall2003 Jr. Literary Gui
Keywords: Elephants